On Sophron fr. 3 K.-A. (Athenaeus 11.480 B). Issue 1 (1st January 2016) - Rodríguez-Noriega Guillén, Lucía
Abstract : After a brief review of some of the general problems posed by Sophron's work, the paper analyses Sophron's fr. 3 K.-A., offering a detailed commentary and a new interpretation of the passage.